Plasma Soluble CD146 as a Potential Diagnostic Marker of Acute Rejection in Kidney Transplantation - Liao, Jun; Fu, Qian; Chen, Wenfang; Li, Jun; Zhang, Wenhui; Zhang, Huanxi; Gao, Yifang; Yang, Shicong; Xu, Bowen; Huang, Huiting; Wang, Jiali; Li, Xirui; et al. (Frontiers in Medicine, 2020)
Previous studies have implicated the role of CD146 and its soluble form (sCD146) in the pathogenesis of inflammatory diseases. However, the association between them and acute rejection in kidney transplant patients remains unexplored. In this study, thirty-four patients with biopsy-proved rejection or non-rejection were retrospectively analysed. Soluble CD146 was detected in peripheral blood by enzyme linked immunosorbent assay (ELISA), and CD146 expression in biopsy was detected by immunohistochemistry. We found that plasma soluble CD146 and CD146 staining in acute rejection recipients were significantly higher than those without rejection. Multivariate analysis demonstrated soluble CD146 as an independent risk factor of acute rejection. The area under the receiver operating characteristic curve (AUC) of sCD146 for AR diagnosis was 0.91, and the optimal cut-off value was 91.5 ng/ml. When combined sCD146 with estimated glomerular filtration rate (eGFR), the area under the curve was 0.96, the sensitivity was 100%, and the specificity was 85.7%, which was significantly better than eGFR alone (P=0.014). Immunohistochemistry showed CD146 expression in glomeruli was positively correlated with Banff-g score, and its expression in tubules also had positive relationship with Banff-t score. Therefore, soluble CD146 may be a potential biomarker of acute rejection, and increasing CD146 expression in the endothelial or tubular epithelial cells may imply the endothelial/epithelial dysfunction involved in the pathogenesis of immune injury.